The Purdah Saga and the muslim woman (2001)
The Purdah saga is an age-long issue in islam, which has generated a lot of controversies. A major problem posed by this saga is the impression that muslim women are barred from outdoor activities or that they must cover their faces when they appear in public. This paper therefore focuses on the Islamic verdict on purdah and the submissions are based on the absolute sources of the Holy Quran and Sunnah